Nursing workload of adult patients hospitalized in an emergency room of a high complexity teaching hospital (Research, Society and Development, 2022)
Introduction: Recognizing the types of care and workload and their oscillation in time in high complexity emergency rooms and their determinants are essential in care management. Despite this there is a scarcity of these data in the literature. Objective: Evaluating the nursing workload of adult patients hospitalized in 2013 and 2019 in different sectors of an emergency room of a teaching hospital of high complexity and open door. Methodology: The types of care, the degree of complexity and the scores of the instrument of the Santos Patient Classification System for adult patients admitted to the emergency room as a function of the subunit were evaluated. Results: The type of care was dependent on the year of sampling for the General Emergency Room, with the high dependence predominated (X2 = 11.43; d.f. = 4; p = 0.022) and for the Clinical Emergency Room with a predominance of intensive care (G = 15.45; d.f. = 4; p = 0.004); while it was not dependent on Clinical-Surgical hospitalization, with the intermediate predominated (G = 1.11; d.f. = 4; p = 0.892). The type of care oscillated between the subunits and reflected the care provided in these units, evidenced when the degree of complexity of care in each subunit was evaluated. Discussion and Conclusion: The results demonstrated the need to evaluate each subunit of the emergency room independently and in time, since they presented different workload profiles. This reflects the specialization, organizational and administrative structure of the emergency room in high complexity units; with a strong impact on patient safety.